Guiding chili variety selection for Zao chili in Guizhou: Based on a systematic study of sensory, physicochemical, and volatile characteristics - Xueya Wang; Kuan Lu; Wenxin Li; Ju Chen; Yong Yin; Xiaojing Sun; Min Lu; Jianwen He (Food Chemistry: X)
This work investigated the influence of seven chili varieties in Guizhou on the quality of Zao Chili (ZC), a local traditional fermented chili product. The physical and chemical indicators, volatile components, and product quality of the seven chili varieties and the ZCs were analyzed. Significant differences in physical and chemical properties among the chili varieties substantially affected the quality of ZCs. Chaotian chilies are harder and spicier, have a higher seed/skin ratio and crude fibre content, and lower fruit weight, water content, and reducing sugar content than Erjingtiao chilies. The Erjingtiao chili FQB3 had the highest reducing sugar content (55.296 g/100 g). The ZC produced by FQB3 had the highest comprehensive sensory score (89.7), characterized by high total acid and amino acid nitrogen content and low crude fibre content. There were 181 volatile compounds in the ZCs, including 32 common compounds and 79 differential compounds. More volatile compounds were found in the ZC derived from Erjingtiao chili. The results combined with the OAV analysis indicated that the aroma profile of ZC could be classified into six attributes, comprising 14 key substances, such as β-damascenone and benzaldehyde. In conclusion, the Erjingtiao chili fulfils ZC's processing requirements. These results will serve as a guide in the assessment of ZC quality, the selection of chili processing varieties, and the stabilization of product quality.